A clinician‐centred programme for behaviour change in the optimal use of staging investigations for newly diagnosed prostate cancer. (16th February 2018) - Rutledge, Alison B.; McLeod, Nicholas; Mehan, Nicholas; Regan, Timothy W.; Ainsworth, Paul; Chong, Peter; Doyle, Terrence; White, Martin; Sanson‐Fisher, Rob W.; Martin, Jarad M.
Abstract : Objectives: To improve imaging utilisation and reduce the widespread overuse of staging investigations, in the form of computed tomography (CT) and whole‐body bone scans for men with newly diagnosed prostate cancer in the Hunter region of NSW, Australia, by implementation of a multifaceted clinician‐centred behaviour change programme. Patients and Methods: Records of all patients with a new diagnosis of prostate cancer were reviewed prior to the intervention (July 2014 to July 2015), and the results of this audit were presented to participating urologists by a clinical champion. Urologists then underwent focused education based on current guidelines. Patterns of imaging use for staging were then re‐evaluated (November 2015 to July 2016). Patients were stratified into low‐, intermediate‐ and high‐risk groups as described by the D'Amico classification system. Results: A total of 144 patients were retrospectively enrolled into the study cohort. The use of diagnostic imaging for staging purposes significantly decreased in men with low‐ and intermediate‐risk disease post intervention. In low‐risk patients, the use of CT decreased from 43% to 0% ( P = 0.01). A total of 21% of patients underwent bone scans in the pre‐intervention group compared with18% in the post‐intervention group ( P = 0.84). In intermediate‐risk patients, the use of CT decreased from 89% to 34% ( P < 0.001), whilst the use of bone scan decreased from 63% to 37% ( P = 0.02). In high‐risk patients, the appropriate use of imaging was maintained, with CT performed in 87% compared with 85% and bone scan in 87% compared with 65% ( P = 0.07). Conclusion: Our results show that a focused, clinician‐centred education programme can lead to improved guideline adherence at a regional level. The assessment of trends and application of such a programme at a state‐based or national level could be further assessed in the future with the help of registry data. This will be particularly important in future with the advent of advanced imaging, such as prostate‐specific membrane antigen positron‐emission tomography.